Eating disorders among professional athletes. A narrative review - Szewczyk, Oliwia; Olek, Ewa; Czarnecka, Karolina; Korczak, Anna; Burda, Katarzyna; Wójcik, Emilia; Łopacińska, Olga; Stańczyk, Katarzyna; Korn, Aleksandra; Jędrzejczyk, Justyna (Quality in Sport, 2024)
Introduction: Eating disorders are potentially mortal health conditions affecting mostly young people. The reasons for that in general population are connected to vulnerable self-image, following the current beauty standards and co-existing psychiatric comorbidities. Athletes may be in danger of developing a pathological eating pattern due to sport specific reasons such as higher scores related to thinner body. Aim of study: The main aim of the study was to examine the relationship between eating disorders in professional athletes’ population, evaluate causes and risk factors and to assess health consequences to eating disorder in sport. Materials and methods: This article is based on the literature found in PubMed and Google Scholar Database with the use of keywords such as ”eating disorders”, “sport”, “athletes”, “anorexia nervosa in athletes”, “eating disorders in sport”, “disordered eating in sportsmen”, “female athletes”, “bulimia nervosa”, “binge eating”, “ED and sport”, “mental health and sport”, “consequences of eating disorders”, “sport education”. Results: Investigation of available literature revealed the connection between developing eating disorder in professional athlete sample. The reasons behind it are mostly sports’ oriented and connected to the desire to achieve better results and perfectionism. However, developing an eating disorder results in worse sports’ performance, menstrual irregularity, lower bone mineral density, cardiovascular issues and can be potentially mortal. Conclusion: Athletes are in danger of developing eating disorders. There should be a focus on evaluating people in sport in terms of eating patterns, however available questionnaires are inefficient because players tend to underreport their problems. Coaches and families of the athletes need to be educated in the topic as they can recognize dangerous behaviors first.